Hands-On Science and Technology : an inquiry approach. - Lawson, Jennifer, 1959- (Hands-on science and technology for Ontario., 2017)
Hands-On Science and Technology: An Inquiry Approach is filled with a year’s worth of classroom-tested activity-based lesson plans. The grade 1 book is divided into four units based on the current Ontario curriculum for science and technology. Needs and Characteristics of Living Things Materials, Objects, and Everyday Structures Energy in Our Lives Understanding Earth and Space Systems This new edition includes many familiar great features for both teachers and students: curriculum correlation charts; background information on the science and technology topics; complete, easy-to-follow lesson plans; reproducible student materials; materials lists; and hands-on, student-centred activities. Useful new features include: the components of an inquiry-based scientific and technological approach Indigenous knowledge and perspective embedded in lesson plans a four-part instructional process—activate, action, consolidate and debrief, and enhance an emphasis on technology, sustainability, and differentiated instruction a fully developed assessment plan that includes opportunities for assessment for, as, and of learning a focus on real-life technological problem solving learning centres that focus on multiple intelligences and universal design for learning (UDL) land-based learning activities FREE access to digital image banks and digital reproducibles (Find download instructions in your book on the reverse side of the title page.)